Deficient operability of the summons within the summary. Its impact on the principle of promptness - De La Torre Garcia, Pamela Michelle (2025)
The summary procedure, due to its legal nature, seeks an expedited process through the reduction of hearings, deadlines, and the simplification of procedures. Therefore, in fulfillment of its purpose, the Organic General Code of Procedures (COGEP), since its entry into force, has structured this type of proceeding with a streamlined process in strict observance of the principle of promptness, aiming for swift and effective resolutions. However, the current justice system is congested, causing delays—even in these types of procedures—directly affecting their legal nature. Considering that the step following the admissibility of the complaint is the service of process, it has been observed in professional practice that this step becomes a bottleneck for various reasons. Cases may take days waiting for service to be completed, causing stagnation in summary procedures. A comparative analysis is carried out regarding the timelines of service of process in summary proceedings, contrasted with a legal and doctrinal analysis of the provisions contained in the Organic General Code of Procedures (COGEP), aimed at ensuring the principle of promptness. Based on the collected information, a proposal will be analyzed to improve the service of process procedures within the judicial system, with the aim of reducing institutional congestion and, more importantly, safeguarding the enforcement of the principle of promptness in summary proceedings while preserving their legal nature.